Pengaruh Beban Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai Di Sekretariat DPRD Kota Samarinda - Naura Dinanti, Nayla; Tri Kusumawati, Yulia; Hadi Saputra, Praja (CV. ITTC INDONESIA, 2025)
Employee performance is a crucial indicator in achieving organizational goals. However, performance can decline when employees face excessive workloads and low levels of job satisfaction. At the Secretariat of the Samarinda City DPRD, there are indications that workload and job satisfaction management are not yet optimal. This study aims to determine the extent to which workload and job satisfaction affect employee performance, both partially and simultaneously. A quantitative approach with a survey method was applied. The study involved all 76 employees, both civil servants and non-civil servants, at the Secretariat of the Samarinda City DPRD, selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using descriptive statistics, validity and reliability testing, classical assumption testing, and multiple linear regression with the help of SPSS. The results show that workload has a significant negative effect on employee performance, while job satisfaction has a significant positive effect. Simultaneously, both variables contribute 26.2% to variations in employee performance. These findings underscore the importance of managing workload proportionally and enhancing job satisfaction to improve employee productivity in public sector organizations. Proper attention to these two factors can significantly support efforts to build an efficient, motivated, and high-performing workforcewithin government institutions.